Monograph review: Fesenko G. G. Morphology of urban landscapes: cultural-philosophical interpretations. – Kharkiv: Ltd. DISA PLUS, 2018. – 282 p. - Карпенко К. І. (Київський національний університет імені Тараса Шевченка, 2018)
The city as a factor of socio-political and cultural life has recently attracted more and more attention of researchers - the mass of diverse literature (art history, cultural studies, sociology, politics, urbanism) dedicated to this issue is constantly growing. However, there are few thorough and original cultural-philosophical works in the domestic philosophical and scientific literature. In our opinion, the monograph of H. G. Fesenko partially fills this lacuna. The author has a good understanding of the objectively complex philosophical and historical-cultural issues, and has also found her own way of understanding them.

Місто як фактор соціально-політичного та культурного життя останнім часом привертає дедалі більше уваги дослідників – маса різноманітної літератури (мистецтвознавство, культурологія, соціологія, політика, урбаністика), присвяченої цій проблематиці, постійно зростає. Однак у вітчизняній філософській та науковій літературі мало ґрунтовних та оригінальних культурно-філософських праць. На нашу думку, монографія Г. Г. Фесенко частково заповнює цю лакуну. Авторка добре розуміє об'єктивно складні філософські та історико-культурні питання, а також знайшла власний спосіб їх осмислення.
Рецензія на монографію: Фесенко Г. Г. Морфологія міських ландшафтів: культурфілософські інтерпретаці. – Харків: ТОВ "ДІСА ПЛЮС", 2018. – 282 с.
Keywords: рецензія; review